Konsep Pendidikan Religio-Humanis Perspektif Soedjatmoko - Al Anhar (DIMAR: Jurnal Pendidikan Islam, 2020)
Soedjatmoko's religious-humanist education concept becomes an educational concept that practically requires a teacher to be sensitive and care about the development and willingness of students. Researchers call it humanist-transcendental education, which is an educational model that gives students freedom of thought based on religious spiritual values. Thus, students should be able to think critically, creatively, innovatively, cooperatively and transcendental, so that their actions always reflect God's goodness. This will also have an impact on a teacher / educator to be more professional, humanist and religious in spirit so that they can become good role models (uswatun hasanah), can be "gugu" and "imitate" and produce students (out-put). who have morals and are able to deliver them to what they aspire to. With a high sense of humanity and a religious attitude that is owned by each teacher / educator and students, this will have an impact on community life to become a civilized society and will make an ideal and humanist education, an education that is superior in achievement. , comfortable and in line with the goals of universal Islamic education.